Effect of two light activated in-office bleaching agents on microhardness of different esthetic restorative materials - Özgün Yusuf Özyılmaz; Tuncay Alptekin; Filiz Aykent; Haluk Barış Kara (Selcuk Dental Journal)
Background: Irradiation sources have been used to reduce the total in-office bleaching time. However, little is known about the effects of the light irradiation bleaching systems on the restorative materials. This in vitro study evaluated the microhardness of 6 different restorative materials during office bleaching procedures with blue light emitted diode and diode laser photoactivation.Materials and Methods: FiltekTM supreme (nanofilled), Tetric EvoCeram (nanohybrid), Tescera ATL (ormocer), Clearfill Majesty Esthetic (nanofilled), Durafill VS (microfilled) and IPS Empress II (ceramic) restorative materials were selected in this study. Twenty specimens, 10 mm in diameter and 2 mm thick, were fabricated from each material using a Teflon mold. All specimens were randomly assigned to two groups (n=10). Group 1 received two topical applications of 35% hydrogen peroxide and was photoactivated using blue light emitted diode (800 mW/cm2) for 20s. Group 2 received topical application of 46% hydrogen peroxide using diode laser (wavelength 980 nm, average power 7 watt, energy setting 200 J, continuous mode) for 30s. Baseline and after bleaching microhardness measurements were taken with a Vickers hardness tester that was used with a 300 g for the porcelain and 100 g for the composite and ormocer specimens, the dwell time was 30 s for all groups. Data were analyzed statistically, with one-way-analysis of variance (ANOVA), post-hoc Tamhane's T2 and independent t tests.Results: After application of both office bleaching agents, microhardness of all restorative materials tested were significantly decreased (p<.05). However, Tetric EvoCeram composite resin material showed the least microhardness value (p<.05).